2007
DOI: 10.1182/blood-2006-12-062471
|View full text |Cite
|
Sign up to set email alerts
|

In vivo vasculogenic potential of human blood-derived endothelial progenitor cells

Abstract: Vascularization of tissues is a major challenge of tissue engineering (TE). We hypothesize that blood-derived endothelial progenitor cells (EPCs) have the required proliferative and vasculogenic activity to create vascular networks in vivo. To test this, EPCs isolated from human umbilical cord blood or from adult peripheral blood, and human saphenous vein smooth muscle cells (HSVSMCs) as a source of perivascular cells, were combined in Matrigel and implanted subcutaneously into immunodeficient mice. Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
457
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 459 publications
(492 citation statements)
references
References 35 publications
25
457
1
9
Order By: Relevance
“…EPCs can be obtained and expanded from HUCBs, and also used for several functions, such as ex vivo expansion of cells similar to ECs for cellular and gene therapy, or, according to Quirici et al [26], in in vitro co-cultures that can provide new perspectives for the treatment of ischemic heart disease. The results obtained by Melero-Martin et al [27] reaffirm SENEGAGLIA, AC ET AL -In vitro formation of capillary tubules from human umbilical cord blood cells with perspectives for therapeutic application the in vivo therapeutic potential of EPCs to form vascular networks that allow for the vascularization of ischemic tissues and organs.…”
Section: Discussionsupporting
confidence: 57%
“…EPCs can be obtained and expanded from HUCBs, and also used for several functions, such as ex vivo expansion of cells similar to ECs for cellular and gene therapy, or, according to Quirici et al [26], in in vitro co-cultures that can provide new perspectives for the treatment of ischemic heart disease. The results obtained by Melero-Martin et al [27] reaffirm SENEGAGLIA, AC ET AL -In vitro formation of capillary tubules from human umbilical cord blood cells with perspectives for therapeutic application the in vivo therapeutic potential of EPCs to form vascular networks that allow for the vascularization of ischemic tissues and organs.…”
Section: Discussionsupporting
confidence: 57%
“…In this study endothelial cells showed positive expression of CD31 for BM (74.2±12) and for UC (87.9±4.5), positive expression of CD34 for BM (83.4±10.4) and for UC (83.7±9.3) and positive double expression of CD31 and CD34 for BM (67.03±8.1%) and for UC (61.9±6.4%). These results were agreed with Erdbruegger et al, [27] and Melero-Martin et al, [28]. Shantsila et al, revealed that; endothelial cells continue to mature (7-14 day) and integrate into the endothelium show homogenous morphology, express CD34, CD31 increases with high in vivo angiogenic effect [29].…”
Section: Discussionsupporting
confidence: 81%
“…[1][2][3][4][5] The vessel walls engineered under these conditions were found to be substantially similar to native vessels at both molecular and cellular levels. [2][3][4][5] These findings have generated considerable interest in the potential application of engineered blood vessels in regenerative medicine and cell-based revascularization therapies. Furthermore, the possibility of establishing a functional vascular network in a surgically accessible location provides an unprecedented opportunity for therapeutic intervention that goes far beyond tissue engineering.…”
Section: Introductionmentioning
confidence: 85%